Penerapan Model Pembelajaran Problem Based Learning dalam Meningkatkan Kemampuan Menulis Teks Laporan Percobaan - Amildayani Amildayani; Muhammad Saleh (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research is motivated by the problems faced by students in writing observation report texts that have not reached the completeness value in learning. The purpose of this study was conducted to understand the level of student success in learning through experimental report text using problem-based learning model on writing skills of class VII students of Mtsn 1 Bone. The type of research used is classroom action research or commonly called PTK with research stages based on 2 cycles. The research refers to the learning process in the classroom. This research uses descriptive, qualitative and quantitative methods. This research was conducted at MTSN 1 Bone. The sample in this study only used 1 class, namely class IX B, which numbered 32 students. The results of the first cycle showed that students lacked understanding of the material if learning was only given theoretically. A total of 32 research subjects stated an increase, indicated by the average value of students in class IX MTsn 1 Bone, which reached 77 higher than the KKM value of Indonesian language subjects which is 75. In the second cycle showed satisfactory success in learning, especially student learning outcomes. Thus, the data results show an increase in students in the second cycle. The average score of students was 89 from the KKM standard score of 75.